I meme nei processi di insegnamento e apprendimento: una semiotica dell’attivazione cognitiva - Petrucco, Corrado (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2022)
Memes have now become a constant presence on social media to connote important social, political and cultural events. Thanks to their communicative power, that with an image and a few lines of text summarizes a concept in an ironic way, their use has also spread in school and university didactic contexts as an innovative mediator in teaching/learning processes. The structure of the meme conveys a concentration of meaning and to be decoded correctly requires a considerable cognitive effort which involves the knowledge of a set of "encyclopedic" elements on a specific disciplinary domain, for example math or literature. Precisely this semiotic characteristic reveals its potential in teaching as a tool for cognitive activation and support for formant evaluation: the teacher can infact propose memes himself or have them made by students: in both cases he will have to verify their correct interpretation by providing immediate feedback about the meanings associated with the meme. However, memes must be used with care since they can also generate cognitive overload and convey cognitive or cultural stereotypes and are to be considered not substitutes but a useful complement to traditional active teaching strategies.